Regulation of persistent infection with herpes simplex virus in vitro by hydrocortisone. - Nishiyama, Y (1979)
About 1% of Raji cells showed sensitivity to herpes simplex virus type 2 (HSV-2) infection when tested by infectious center assays or immunofluorescence tests, and the percentage did not change during cell passage. The addition of hydrocortisone to Raji cells persistently infected with HSV-2 caused a marked increase in virus production and in the number of HSV-producing cells. In the case of HSV-1, it was shown that the addition of hydrocortisone was required to maintain persistent infection. These observations suggest that control of replication of HSV-1 and HSV-2 in these cells is regulated by different mechanisms.